Fundamentals of database systems - Elmasri, Ramez; Navathe, Shamkant B. (Hoboken, NJ : Pearson, 2016)
"This book introduces the fundamental concepts necessary for designing, using, and implementing database systems and database applications. Our presentation stresses the fundamentals of database modeling and design, the languages and models provided by the database management systems, and database system implementation techniques"--Page vii.
Databases and Database Users -- Database System Concepts and Architecture -- Data Modeling Using the Entity-Relationship (ER) Model -- The Enhanced Entity-Relationship (EER) Model -- The Relational Data Model and Relational Database Constraints -- Basic SQL -- More SQL: Complex Queries, Triggers, Views, and Schema Modification -- The Relational Algebra and Relational Calculus -- Relational Database Design by ER- and EER-to-Relational Mapping -- Introduction to SQL Programming Techniques -- Web Database Programming Using PHP -- Object and Object-Relational Databases -- XML: Extensible Markup Language -- Basics of Functional Dependencies and Normalization for Relational Databases -- Relational Database Design Algorithms and Further Dependencies -- Disk Storage, Basic File Structures, Hashing, and Modern Storage Architectures -- Indexing Structures for Files and Physical Database Design -- Strategies for Query Processing -- Query Optimization -- Introduction to Transaction Processing Concepts and Theory -- Concurrency Control Techniques -- Database Recovery Techniques -- Distributed Database Concepts -- NOSQL Databases and Big Data Storage Systems -- Big Data Technologies Based on MapReduce and Hadoop -- Enhanced Data Models: Introduction to Active, Temporal, Spatial, Multimedia, and Deductive Databases -- Introduction to Information Retrieval and Web Search -- Data Mining Concepts -- Overview of Data Warehousing and OLAP -- Database Security -- Appendix A, Alternative Diagrammatic Notations for ER Models -- Appendix B, Parameters of Discs -- Appendix C, Overview of the QBE Language -- Appendix D, Overview of the Hierarchical Data Models -- Appendix E, Overview of the Network Data Model.
Includes bibliographical references and index.
AAL
Parama
Keywords: Database management; Computer science